2006
DOI: 10.1097/00042737-200604000-00008
|View full text |Cite
|
Sign up to set email alerts
|

An evidence-based, Latin-American consensus on gastro-oesophageal reflux disease

Abstract: In recognition of the high prevalence of gastro-oesophageal reflux disease (GORD) and its importance in Latin America, the InterAmerican Association of Gastroenterology and the InterAmerican Society of Digestive Endoscopy organized a Latin-American Consensus on GORD in Cancun, Mexico in September 2004. The main objectives of the consensus meeting were to provide evidence-based guidance with respect to the diagnosis and treatment of GORD, relevant to all countries in the region. The methodology, results and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 126 publications
1
7
0
1
Order By: Relevance
“…These agents are more effective than placebo for the relief of symptoms as empiric therapy and also for NERD; however, they are less effective than PPIs. 1,26 Review outcome: No relevant studies on H 2 -RAs were published during the review period. Impact on Recommendations: None.…”
Section: Diet and Lifestyle Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…These agents are more effective than placebo for the relief of symptoms as empiric therapy and also for NERD; however, they are less effective than PPIs. 1,26 Review outcome: No relevant studies on H 2 -RAs were published during the review period. Impact on Recommendations: None.…”
Section: Diet and Lifestyle Changesmentioning
confidence: 99%
“…1 The implementation of consensus guidelines poses two main challenges: ensuring timely dissemination of the guidelines to all stakeholders, while, in conjunction, maintaining a current evidence base such that the guidelines remain relevant to clinical practice. A review of the literature published after the Latin American consensus revealed a detailed consideration of the definitions of GERD from a global perspective 2 ; in contrast, there were no significant publications addressing important features of diagnosis.…”
mentioning
confidence: 99%
“…É improvável que pacientes com DTNC não relacionada com a DRGE e que não apresentem sintomas de alarme, possam demonstrar achados endoscópicos significativos. Por outro lado, a avaliação endoscópica continua sendo importante para descartar a presença de esofagite péptica e/ou infecciosa (monilíase) e para descartar afecções de maior gravidade como esôfago de Barrett e câncer de esôfago (5,9) .…”
Section: Teste Terapêutico Com Inibidor Da Bomba Protônica (Ibp)unclassified
“…Worldwide, several consensus groups have developed treatment guidelines for the management of GERD [18][19][20][21][22]; however, there is inconsistency with respect to the first-line management approach (either diagnostic work-up or medication first) and treatment duration in cases where medication is recommended first (varies from 1 to 8 weeks). Although the switch from prescription to OTC status is growing, this has not translated to specific recommendations on OTC treatment in recent evidence-based guidelines for the management of GERD [20,23].…”
Section: Introductionmentioning
confidence: 99%
“…Although the switch from prescription to OTC status is growing, this has not translated to specific recommendations on OTC treatment in recent evidence-based guidelines for the management of GERD [20,23].…”
Section: Introductionmentioning
confidence: 99%